The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00268-004-7610-2
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Survival of Patients with Small Intestinal Carcinoid Tumors

Abstract: Midgut carcinoid tumors are rare and have a markedly better prognosis than adenocarcinoma in the small intestine. New diagnostic methods and medical as well as surgical therapies have evolved during the last decades, leading to more active care of these patients. Patients with small intestinal carcinoids diagnosed from 1960 to 2000 in the duodenum (n = 89) and jejunum/ileum (n = 2437) were identified in the Swedish Cancer Registry. Cases without histologic verification and autopsy cases were excluded. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
7
36
1
4
Order By: Relevance
“…Advanced age has been found to be related to worse overall survival as well as disease-specific and relative survival in multiple studies (Greenberg et al 1987, Janson et al 1997, Gibril et al 1998, Quaedvlieg et al 2001, Solorzano et al 2001, Zar et al 2004, Asamura et al 2006, Clancy et al 2006, Lepage et al 2007, Rea et al 2007. Our study does not allow for discriminating the putative roles of co-morbid conditions, tolerance to therapy and/or tumor aggressiveness associated to increased age.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Advanced age has been found to be related to worse overall survival as well as disease-specific and relative survival in multiple studies (Greenberg et al 1987, Janson et al 1997, Gibril et al 1998, Quaedvlieg et al 2001, Solorzano et al 2001, Zar et al 2004, Asamura et al 2006, Clancy et al 2006, Lepage et al 2007, Rea et al 2007. Our study does not allow for discriminating the putative roles of co-morbid conditions, tolerance to therapy and/or tumor aggressiveness associated to increased age.…”
Section: Discussionmentioning
confidence: 60%
“…This is particularly true in GEP tumors that can be associated with a diverse natural history. Epidemiological studies of GEP NET have reported increase age as a major prognostic feature (Quaedvlieg et al 2001, Zar et al 2004, Lepage et al 2007) but conflicting results regarding the prognostic effect of gender (Beasley et al 2000, Quaedvlieg et al 2001, Modlin et al 2003, Zar et al 2004, Tomassetti et al 2006, Lepage et al 2007. Additionally, in previous multivariate analysis from tertiary referral centers, pathological differentiation and stage at diagnosis have been identified as the strongest prognostic features of GEP NET.…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, increased earlier detection of NETs of the small intestine has led to improved prognosis [15,16] . The five year survival rate of patients with NETs of the small intestine in the SEER Register has gone up from 51.9% in the 1970s and 1980s to 60.5% in the 1990s [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on patients, registered in the Swedish Cancer Registry, with small intestinal carcinoids diagnosed from 1960 to 2000 in the duodenum (n= 89) and jejunum/ileum (n=2437), the overall 5-, 10-, and 15 year survivals were, respectively, 60, 46, and 28% for duodenal tumors and 56, 36, and 23% for jejunal/ileal tumors (Zar et al, 2004).…”
Section: Small Intestinal Carcinoidsmentioning
confidence: 99%